The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2621.2006.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protein level and starch type on an extrusion‐expanded whey product

Abstract: A whey-based puffed snack food was produced on a twin-screw extruder to determine the effect of varying starch type (normal corn and pregelatinised waxy), protein type (regular and instantised whey protein concentrate) and protein concentration (16%, 32% and 40%) on the physical and chemical characteristics of an extruded-expanded snack food. Increasing protein concentration and normal cornstarch significantly reduced extrudate expansion ratio, air cell size, water solubility index and increased extrudate dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 14 publications
6
120
1
2
Order By: Relevance
“…Addition of WPI increased expansion also in the studies of Agbisit (2007) and Kirjoranta et al (2012). On the contrary, in the studies of Matthey and Hanna (1997); Onwulata et al (1998Onwulata et al ( , 2001 and Allen et al (2007) addition of whey protein concentrate (WPC) decreased expansion of extrudates. It has been speculated that other components in WPC, such as lactose, caused low expansion (Onwulata et al 2001).…”
Section: Properties Of the Extrudatesmentioning
confidence: 87%
See 3 more Smart Citations
“…Addition of WPI increased expansion also in the studies of Agbisit (2007) and Kirjoranta et al (2012). On the contrary, in the studies of Matthey and Hanna (1997); Onwulata et al (1998Onwulata et al ( , 2001 and Allen et al (2007) addition of whey protein concentrate (WPC) decreased expansion of extrudates. It has been speculated that other components in WPC, such as lactose, caused low expansion (Onwulata et al 2001).…”
Section: Properties Of the Extrudatesmentioning
confidence: 87%
“…26 %), which has a mainly linear structure (Moraru and Kokini 2003). It has been suggested that linear amylose molecules may align themselves or form complexes with other molecules such as whey proteins by hydrogen bonds causing decrease in expansion and increase in hardness (Allen et al 2007;Matthey and Hanna 1997). On the contrary, with waxy starch, protein-protein interactions are favoured instead, which is found to increase expansion and decrease hardness (Allen et al 2007;Matthey and Hanna 1997).…”
Section: Properties Of the Extrudatesmentioning
confidence: 91%
See 2 more Smart Citations
“…Fibers also affect the expansion of the product. Fibrous fragments disrupt the starchy film of air cell walls, reducing their formation and swelling and altering air cell size (Huber, 2001;Allen et al, 2007).…”
Section: Resultsmentioning
confidence: 99%